Novice special education teachers' problems and coping strategies - Mendoza, Cristina L.; Adorio, Mercedes P.; Soria, Robinson C.; Manzano, Virgilio U.; Otero, Marietta Reyes (Quezon City College of Education, University of the Philippines Diliman, 2007)
This research is a survey of problems, concerns, strong points, areas for improvement, coping strategies, and recommendations of Special Education teachers in their first year up to their first three years of teaching. The study used the descriptive, normative type of research particularly the survey type. Findings showed that novice SpEd teachers are very concerned about the lack of instructional materials, meeting the needs of their students, and more generally, of their aptitude and adequacy as a teacher. Based in their self-evaluation, their strong points are their patience, sensitivity to the needs of each student, and hard-working and commitment to work. Novices can improve themselves by taking graduate courses, participating in training programs, and/or by looking for a mentor.
Thesis (Master of Arts in Education - Special Education)--University of the Philippines, Diliman
Keywords: Special education teachers -- Philippines -- Manila Metropolitan Area